Valuasi Ekonomi Lingkungan Southlake Mutiara Gading City, Kabupaten Bekasi - Citra Nur Izati (Yayasan Literasi Sains Indonesia, 2026)
South Lake Mutiara Gading City (MGC) is an artificial lake area utilized as a tourism destination as well as a supporting facility for a residential area in Bekasi Regency. This area provides environmental and economic benefits, although no entrance fee has been applied to visitors to date. This study aims to estimate the environmental economic value of South Lake MGC and to identify factors influencing visitor frequency. The study employed the Individual Travel Cost Method (ITCM) combined with multiple linear regression analysis based on data collected from 37 visitors. The analyzed variables included travel cost, age, education level, income, length of visit, group size, cleanliness quality of the tourism area, and toilet facilities. The estimated consumer surplus was Rp 21.018 per visit. Based on an average annual visitation of 7.800 visitor, the total environmental economic value of South Lake MGC is estimated at Rp 163.939.113 per year. These findings are expected to serve as a reference for tourism area managers in formulating management policies, particularly in determining appropriate entrance fees and improving facility quality to support sustainable tourism development. This levy is a payment mechanism for environmental services (PES) that can encourage environmental benefits to be considered in real terms in terms of economic value. This study calculates the economic valuation of an artificial lake within a modern residential area, whose ecological function is often considered merely aesthetic. The lack of environmental economic valuation research at this location served as the basis for this research.